Functional knee phenotypes - A novel classification for the lower limb alignment based on the native alignment in young non-osteoarthritic patients. Issue 5 (28th May 2020) - Moser, Lukas; Hess, Silvan; Behrend, Henrik; Hirschmann, Michael
Aims and Objectives: In total knee arthroplasty (TKA), the postoperative coronal alignment is a key factor for good clinical outcome. At the same time, the optimal alignment has been under debate recently. This debate usually focuses on the overall limb alignment while the details of the alignment, such as femoral or tibia alignment, are neglected. This might be partly because there is no concept which incorporates all parameters in a comprehensive and simple way. The purpose of this study was therefore to establish such a concept for the coronal knee alignment. Materials and Methods: The hospital registry was searched for patients older than 16 and younger than 45 years, who received a CT according to the Imperial Knee Protocol. Patients with prosthesis, osteoarthritis, fractures or injury of the collateral ligaments were excluded. Finally, 308 non-osteoarthritic knees of 160 patients remained (102 males and 58 females, mean age ± standard deviation (SD) 30±7 years). The following coronal alignment parameters were measured using a validated software (KneePLAN 3D, Symbios Orthopédie S.A): hip-knee-ankle angle (HKA, angle formed by the lines connecting the centers of the femoral head, the knee and the talus), femoral mechanical angle (FMA, angle between the mechanical axis of the femur and the tangent to the distal femoral condyles) and tibial mechanical angle (TMA, angle between the mechanical axis of the tibia and the tangent to the tibial plateau). Phenotypes for the limb, femur and tibia were defined based on these measurements. A phenotype thereby consists of a phenotype specific mean value (HKA, FMA or TMA value) and covers a range of ± 1.5° from this mean (e.g. 180°± 1.5). The phenotype specific mean values represent 3° increments of the angle starting from the rounded overall mean value of the angle. Results: Out of 125 possible phenotypes, 43 were found in these non-osteoarthritic knees (35 male, 26 female and 18 mutual phenotypes). The most common functional knee phenotype in males was NEUHKA0°NEUFMA0°NEUTMA0° (19%), followed by VARHKA3°NEUFMA0°VARTMA0° (8.2%). The most common phenotype in females was NEUHKA0°NEUFMA0°NEUTMA0° (17.7%), closely followed by NEUHKA0° NEUFMA0°VALTMA0° (16.6%). Conclusion: The functional knee phenotype concept better represents the variability of the coronal knee alignment than the conventional system of valgus, varus and neutral. Furthermore, it should enable a more detailed discussion about the coronal alignment and TKA alignment goals.